Cigarette Smoking and Chronic Kidney Disease in African Americans in the Jackson Heart Study. Issue 6 (25th May 2016) - Hall, Michael E.; Wang, Wei; Okhomina, Victoria; Agarwal, Mohit; Hall, John E.; Dreisbach, Albert W.; Juncos, Luis A.; Winniford, Michael D.; Payne, Thomas J.; Robertson, Rose M.; Bhatnagar, Aruni; Young, Bessie A.
Abstract : Background: Controversy exists regarding the association of cigarette smoking and renal dysfunction, particularly among African Americans, who are disproportionately affected by chronic kidney disease; therefore, we evaluated the relationship between cigarette smoking and rapid renal function (RRF) decline in the Jackson Heart Study. Methods and Results: Rates of RRF decline were determined among 3648 African American participants enrolled at baseline in the Jackson Heart Study. RRF decline was defined as an absolute decline of estimated glomerular filtration rate of 30% from visit 1 to visit 3. There were 422 current, 659 past, and 2567 never smokers identified at visit 1. After adjustment for age, sex, body mass index, diabetes, hypertension, cholesterol, physical activity, education, alcohol consumption, and prevalent cardiovascular disease, current smokers demonstrated a significantly higher incidence of RRF decline compared with never smokers (incidence rate ratio 1.83, 95% CI 1.31–2.56). Current smokers using 1 to 19 and ≥20 cigarettes daily had an increased incidence of RRF decline (incidence rate ratios of 1.75 [95% CI 1.18–2.59] and 1.97 [95% CI 1.17–3.31], respectively). There was a significant, progressive reduction in estimated glomerular filtration rate from visit 1 to visit 3 in current and past smokers compared with never smokers. Finally, current smokers had a 1.38‐fold increase in C‐reactive protein compared with never smokers, after controlling for covariates. Conclusions: In a large African American cohort, current cigarette smoking was independently associated with RRF decline in a dose‐dependent manner. There was also evidence of increased inflammation (C‐reactive protein) in current smokers, suggesting a potential mechanism for these relationships.